52nd IEEE Conference on Decision and Control 2013
DOI: 10.1109/cdc.2013.6760942
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis for systems with saturation and backlash in the loop

Abstract: This paper deals with the stability analysis problem for linear systems with saturation and backlash in the loop. The resulting system controlled by a static output feedback is a dynamical model with nested backlash and saturation operators. Uniform ultimate boundedness stability is tackled in a regional (local) or global context depending on the stability property of the open-loop system. Suitable regions of the state space in which the closed-loop trajectories can be captured are characterized, together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…and M 1 defined in (14), recalling that W = P −1 . The satisfaction of relations (13) and (15) implies both L 0 < 0 and ρ LT 3 Lρ − τ ≤ 0, and then L < 0, for all (x, ϕ 1 , Ψ 1 ,Ψ 1 ) = 0.…”
Section: B Regional Stabilitymentioning
confidence: 97%
See 3 more Smart Citations
“…and M 1 defined in (14), recalling that W = P −1 . The satisfaction of relations (13) and (15) implies both L 0 < 0 and ρ LT 3 Lρ − τ ≤ 0, and then L < 0, for all (x, ϕ 1 , Ψ 1 ,Ψ 1 ) = 0.…”
Section: B Regional Stabilitymentioning
confidence: 97%
“…Proposition 3.1: Theorem 3.1 enjoys the following properties: 1) Given E c = 0, condition (13) is feasible if matrix A 0 is Hurwitz. 2) There always exists E c non null such that condition (13) holds, if matrix A 0 is Hurwitz. Proof: In [15], it has been shown that M 0 < 0 is feasible if matrix A 0 is Hurwitz (that is there exist τ , W , T 3 and S 2 such that M 0 < 0).…”
Section: Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing generalized sector conditions, stability for systems with backlash and saturation is studied in [16].…”
Section: Compensation For Combined Backlash and Saturationmentioning
confidence: 99%